Information need and information seeking behaviour of engineering college students in Madurai - a case study - Chinnasamy, K. (Qualitative and Quantitative Methods in Libraries; Vol 5 No 1 (2016): March 2016 Issue, 2017)
This case study investigated information need and seeking behaviour of information behaviour of engineering college students in Madurai. The main objective of study seeking behaviour of engineering college students to the information literacy and study the purpose and motives of the students seeking information. Data was collected through a pre-tested questionnaire, using the snowball sampling technique. So only 300 respondents are used for in data analysis and interpretation. It was found that 55.33% respondents are using the library for Preparing for the examination, 38% respondents are suing the print copy and 81.33% respondents are using the pen drive. Libraries have always welcomed new changes for enhancing their services and satisfactory clientele‟s needs. It‟s a high time for traditional libraries that they change their approach as the availability of the digital resources is growing day by day. The paper suggests certain measures for improving information need skills of students to make them more competent information users.